Rare carcinoma ex pleomorphic adenoma of the buccal minor salivary gland causing a therapeutic dilemma - Yogesh Kini; Chirag Desai; Uma Mahindra; Jitendra Kalburge (Wolters Kluwer Medknow Publications, 2012)
Carcinoma ex pleomorphic adenoma (CXPA), as a group, constitutes 12% of malignant salivary gland tumors. We present a case of CXPA of the buccal mucosa in a 17-year-old patient. The buccal mass was of a size of 3.0 cm located in the right cheek. Pleomorphic adenoma was the provisional diagnosis. The tumor was excised under local anesthesia. Histopathological evaluation revealed a pre-existing pleomorphic adenoma. However, on magnification, certain areas showed islands of dysplastic epithelial cells' invading the fibrous capsule and CXPA was diagnosed. The patient was recalled and secondary surgery of the site performed. No tumor tissue could be detected in the secondary resection specimen. There is no sign of recurrence since 2 years.